Prognostic value of albumin-bilirubin grade in lung cancer: a meta-analysis - Jiao Jiang; Hongjuan Li; Lin Chen; Xiaoming Qiu (Journal of Cardiothoracic Surgery)
Abstract Purpose To clarify the prognostic role of pretreatment albumin-bilirubin (ALBI) grade in lung cancer patients. Methods The PubMed, EMBASE, Web of Science and CNKI databases were searched up to April 20, 2024. Primary outcomes included the overall survival (OS), progression-free survival (PFS) and cancer-specific survival (CSS). Hazard ratios (HRs) with 95% confidence intervals (CIs) were combined and subgroup analysis based on the type of lung cancer [non-small cell lung cancer (NSCLC) vs. small cell lung cancer (SCLC)] and treatment [surgery vs. immune checkpoint inhibitors (ICIs) vs. chemotherapy] was conducted. Results Eight studies with 2,057 patients were included. Pooled results indicated that elevated pretreatment ALBI grade was significantly related to poor OS (HR = 2.50, 95% CI: 2.03–3.09, P<0.001), PFS (HR = 1.91, 95% CI: 1.56–2.33, P<0.001) and CSS (HR = 1.90, 95% CI: 1.11–3.11, P = 0.018). Subgroup analysis for OS based on the pathological type and primary treatment manifested similar results. Conclusion Pretreatment ALBI grade is associated with prognosis in lung cancer and patients with elevated ALBI grade are more likely to experience worse survival.